"I feel freer here": engaging older men in mental health-promoting communities through a Shared Reading intervention - Mette Marie Kristensen; Anna Paldam Folker; Andreas Melson Gregersen; Lars Berg Schovsbo; Nana Cecilie Halmsted Kongsholm (Journal of Men's Health)
Background: Older men face higher rates of chronic illness, mental health challenges and social isolation, exacerbated by traditional masculinity norms that discourage emotional openness and help-seeking. Retirement and aging can further disrupt their social roles and identity, contributing to poorer well-being. Shared Reading, a reading group concept for guided collective engagement with literary texts, has shown potential to improve mental health outcomes and foster community among older men. This study aims to explore how Shared Reading may engage older men in health-promoting communities. Methods: The study was a qualitative exploration of a Shared Reading intervention targeting men aged 60 and above. It was based on six site visits to local Shared Reading group locations across Denmark, including interviews with local reading guides, participants in the Shared Reading groups across the sites, and the intervention project management. Results: We identified three central mechanisms for engagement across the Shared Reading groups: (1) the literature, serving as a common objective, a tool, and a window for the male participants; (2) the all-male setting, creating a safe space where the men felt more authentic, and (3) the combination of the all-male safe space and attributes of the literature created a confidential community, where participants felt at home and able to let their guards down. Based on these findings, we suggest that Shared Reading may be an effective way to engage men in mental health-promoting communities. Conclusions: The study highlights the broader implications of Shared Reading for mental health promotion among men. It demonstrates the importance of creating safe, activity-based and gender-sensitive interventions that resonate with male participants while subtly challenging traditional norms of masculinity. On this basis, we suggest that Shared Reading offers a framework for promoting mental well-being and provides valuable insights into the potential of literature for fostering connection and emotional exploration in male communities.